2018
DOI: 10.1080/20961790.2018.1521327
|View full text |Cite
|
Sign up to set email alerts
|

Digital capture of fingerprints in a disaster victim identification setting: a review and case study

Abstract: Identification of victims following a mass fatality is conducted by collecting and analysing a series of scientific identifiers and contextual information of each decedent. Recently, there has been a paradigm shift demanding that this complex identification process be accelerated to meet the needs of the surviving families, politicians and even the media. Postmortem fingerprint identification is a fast and efficient means of victim identification, and through the use of new advances in technology, the digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
0
12
0
4
Order By: Relevance
“…In real time, those victims that had not been directly identified by the Alethia AFIS had their friction ridge details accessed remotely and added to Brazil’s national AFIS. The biometric scanner uses optical technology, which enables the collection of friction ridge information from the victims’ bodies [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In real time, those victims that had not been directly identified by the Alethia AFIS had their friction ridge details accessed remotely and added to Brazil’s national AFIS. The biometric scanner uses optical technology, which enables the collection of friction ridge information from the victims’ bodies [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other procedures, such as personal descriptions, tattoos, medi­cal findings, among others, are classified as secondary methods [ 5 ]. Friction ridge analysis is considered the fastest primary identification method [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current research into technology for DVI focuses on data collection at the scene, e.g., digital capture of fingerprints [10]; pathology technology to assist the post-mortem phase [11]; or data management and matching at the reconciliation phase [12]. Fewer studies focus on the linkage of physical remains and digital data, or related problems such as the tracking of living victims of disaster.…”
Section: Examples Of Technology In DVI Practicementioning
confidence: 99%
“…All victims in this study were identified using the acquisition method + smartphone image. Johnson and Riemen (2019) presented a review on digital fingerprint acquisition in DVI victims, citing smartphones as an option, with low technology, easy internet connection, and images with the necessary quality for human identification results.…”
Section: Smartphone Versus Standard Cameramentioning
confidence: 99%